Heightened Local Th17 Cell Inflammation Is Associated with Severe Community-Acquired Pneumonia in Children under the Age of 1 Year. (22nd September 2021) - Liu, Ming; Lu, Bingtai; Fan, Huifeng; Guo, Xuanjie; Du, Shuling; Yang, Diyuan; Xu, Yiping; Li, Yue; Che, Di; Liu, Yunfeng; Gu, Xiaoqiong; Ding, Tao; et al.
Abstract : Severe community-acquired pneumonia (sCAP) early in life is a leading cause of morbidity, mortality, and irreversible sequelae. Herein, we report the clinical, etiological, and immunological characteristics of 62 children age < 1 year. We measured 27 cytokines in plasma and bronchoalveolar lavage (BAL) from 62 children age < 1 year who were diagnosed with CAP, and then, we analyzed correlations among disease severity, clinical parameters, and etiology. Of the entire cohort, three cytokines associated with interleukin-17- (IL-17-) producing helper T cells (Th 17 cells), IL-1 β, IL-6, and IL-17, were significantly elevated in sCAP patients with high fold changes (FCs); in BAL, these cytokines were intercorrelated and associated with blood neutrophil counts, Hb levels, and mixed bacterial-viral infections. BAL IL-1 β (area under the curve (AUC) 0.820), BAL IL-17 (AUC 0.779), and plasma IL-6 (AUC 0.778) had remarkable predictive power for sCAP. Our findings revealed that increased local Th 17 cell immunity played a critical role in the development of sCAP in children age < 1 year. Th 17 cell-related cytokines could serve as local and systemic inflammatory indicators of sCAP in this age group.